Examining the Effect of a Medication Synchronization or an Education Program on Health Outcomes of Hypertensive Patients in a Community Pharmacy Setting - Kristen L. DiDonato; Kristin R. Vetter; Yifei Liu; Justin R. May; D. Matthew Hartwig (INNOVATIONS in Pharmacy, 2014)
Objective: To examine the effect of a medication synchronization or education program on hypertensive health outcomes.